Estimation of Internal Gearbox Loads for Condition Monitoring in Wind Turbines Based on Physical Modeling. (October 2020) - Pagitsch, M; Jacobs, G; Bosse, D; Duda, T
Abstract: The share of wind energy in the public electricity supply in Europe is constantly growing, so that reliability and availability of wind turbines are becoming increasingly important. High availability is ensured by continuous condition monitoring, because it allows long downtimes to be avoided by reacting immediately to (imminent) failures. This paper presents a portable and real-time capable simulation model for determining internal loads on components in the mechanical drivetrain. The loads are apt for being utilized for a subsequent generation of a system reliability index in the scope of a decision support tool for demand- and degradation-oriented adjustments of the operational management. Thus, the work contributes to ensuring reliability. By determining the state of degradation of similarly loaded plants, under- or overloading of individual turbines can be proactively prevented. The analysis of the influence of individual model parameters is of particular importance here and provides evidence that even with a restricted parameter set the outputs of the load calculation model are accurate enough as inputs for a reliability calculation.